Making Cyprus a national cause in Turkey's foreign policy, 1948-1965 - ÖZKAN, BEHLÜL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2015)
As the global wave of decolonization that began after 1945 reached the island of Cyprus, the Cyprus question turned into an issue of paramount importance for Turkish nationalists and for the Turkish people in general. Long before, Turkish foreign policy architects - who had previously taken the line that 'Turkey does not have a Cyprus problem' - came to portray Cyprus as a 'national cause'. Three different geopolitical discourses were instrumental in legitimizing Turkey's claims over Cyprus and in leading Turkish society to believe that it had a crucial stake in the fate of the island. Naturalized geopolitics represented Cyprus as a natural extension of the Turkish heartland, while ideological geopolitics put forth that Greek Cypriots were responsible for the spread of communism. Finally, civilizational geopolitics characterized Turkey and Greece's rivalry in Cyprus as the latest chapter in the centuries-old conflict between Turkishness and Hellenism.
Keywords: Turkish nationalism; geopolitics; Turkish foreign policy; national homeland; Cyprus